2017
DOI: 10.1016/j.ijid.2017.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Is Leishmania (Viannia) braziliensis parasite load associated with disease pathogenesis?

Abstract: The data revealed a tendency to higher tissue parasitism in the skin compared to mucous lesion sites and a reduction with disease progression. Parasite load was lower in poor compared to good responders to antimonials, and was also reduced in recurrent lesions compared to primary ones. However, parasite load became higher with sequential relapses, pointing to an immune system inability to control the infection. Therefore the parasite burden does not seem to be a good predictor of disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 25 publications
3
17
1
Order By: Relevance
“…The Lb/IGS primer system presented a satisfactory performance in optimization tests and exhibited a high sensitivity for the detection of L. braziliensis in assays with 98.08% analytical efficiency. These results showed a higher efficiency when compared to other similar studies [ 10 , 46 ]. The cross reaction obtained only for species of the Viannia subgenus emphasizes the high genetic similarities among them.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…The Lb/IGS primer system presented a satisfactory performance in optimization tests and exhibited a high sensitivity for the detection of L. braziliensis in assays with 98.08% analytical efficiency. These results showed a higher efficiency when compared to other similar studies [ 10 , 46 ]. The cross reaction obtained only for species of the Viannia subgenus emphasizes the high genetic similarities among them.…”
Section: Discussionsupporting
confidence: 50%
“…The infections caused by L. braziliensis correspond to lesions with scarce parasites. In this case, qPCR might be useful to confirm the diagnosis, besides evaluating the parasitic load, providing advantages once infections caused by this species may evolve to mucocutaneous form, which requires differentiated clinical and therapeutic management [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…requires the quantification of both parasites and the host cells (by means of another qPCR for a single copy host gene). The comparison of the two qPCR results allows to obtain the number of parasites/number of host cells [ 13 , 33 , 34 , 48 , 76 , 77 ]. Alternatively, if yield of DNA extraction is reproducible among different samples and the amount of DNA can be accurately determined, the number of parasites could also be normalized to μg of tissue DNA [ 78 ].…”
Section: Qpcr Assays For Parasite Detection and Quantificationmentioning
confidence: 99%
“…Although studies on experimental infection showed initial inocula impacted on clinical course, the parasite burden detected in established lesion may not influence the therapeutic response since Pereira et al (2017) demonstrated high parasitism in good responders when compared with the poor ones ( Pereira et al, 2017 ). However, there was an increase in parasite burden with recurrent relapses which suggests a failure of the immune system in controlling the parasite replication ( Pereira et al, 2017 ).…”
Section: Parasite Point Of View: Do Parasites Influence the Therapeutmentioning
confidence: 99%